2009
DOI: 10.13181/mji.v18i4.375
|View full text |Cite
|
Sign up to set email alerts
|

High intensity interior aircraft noise increases the risk of high diastolic blood pressure in Indonesian Air Force pilots

Abstract: AbstrakTujuan Untuk menganalisis apakah bising pesawat terbang denyut nadi istirahat, dan faktor lain berperan meningkatkan risiko kejadian tekanan darah diastolik (TDD) pada penerbang TNI AU. Metode Desain penelitian nested case-control. Data berasal dari rekam medis hasil pemeriksaan kesehatan berkala dan indoktrinasi latihan aerofi siologi di LAKESPRA Saryanto di Jakarta antara Januari 2003 -September 2008. Kelompok kasus ialah subjek dengan TDD ≥90 mmHg; kelompok kontrol adalah dengan TDD ≤89 mmHg. Setiap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Title and abstract screening, citation tracking, and the reference list search identified 180 studies for the full text screening. We included 24 studies published (in 26 publications) between 1977 and 2019 [ 44 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. Despite extensive searching, we were unable to obtain the complete text of six publications through our library and excluded 148 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Title and abstract screening, citation tracking, and the reference list search identified 180 studies for the full text screening. We included 24 studies published (in 26 publications) between 1977 and 2019 [ 44 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. Despite extensive searching, we were unable to obtain the complete text of six publications through our library and excluded 148 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the sex of the working populations considered, 13 of the studies recruited both male and female participants, although men comprised over 70% of the participants in seven of these studies. One study recruited only female participants [ 72 ], six recruited only male participants, and three studies [ 64 , 65 , 67 ] did not provide any information on the sex of the participants. However, due to the occupations that were considered by these studies and the sex distribution reported by other studies considering comparable occupations, we presume these study populations were predominately, if not entirely, male.…”
Section: Resultsmentioning
confidence: 99%
“…the type of aircraft, (fixed wing planes or helicopters), the length of employment (2 -10, and 11 -25 years), age on diagnosis (23-29, 30-39, and 40-48 years), age at starting work (19 -22, and 23 -26 years), rank (first officers that are second lieutenant to captain and middle-ranked officers that are major until colonel), total flight hours (147-1400, and 1401-11.125 hours), annual average flight hours (29-299, and 300-622 hours/year), and year of starting work (year 1980 -1990 and 1991 -2003). 12 Further, data that may be related to hypertension were also collected, i.e. fasting blood glucose level (less than or equal to 126, and greater than 126 mg/dL), blood cholesterol level (less than or equal to 200, and more than 200 mg/dL), BMI (18.00-22.99, 23.00-24.99, and 25.00-39.00 kg/m 2 ), 14 waist circumference (normal ≤90, and high> 90 cm), resting pulse rate (50-80, and 81-101/minute), resting pulse pressure (10-40, and 41-90 mmHg).…”
Section: Data Collectionmentioning
confidence: 99%
“…Grouping of variables were based on the ROC curves. 12 All the data collected were checked manually for completeness and consistency before data processing. Verification of the data was done visually for any errors.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation